Tugas dan Fungsi Badan Keuangan dan Aset Daerah dalam Mengimplementasikan Desentralisasi Kebijakan demi Menjamin Efisiensi dan Transparansi Pengelolaan Keuangan Daerah di Kota Kupang - Giovanni Secondoi Putra Himan; Saryono Yohanes; Agnes Doortji Rema (Pusat Riset dan Inovasi Nasional, 2025)
The management of regional finances aims to realize good governance that includes efficiency and transparency in meeting public needs. Efficiency and transparency in the decentralization of financial management policy by the Financial and Asset Management Agency (BKAD) of Kupang City are key factors in ensuring proper regional financial management. This study uses an empirical research method. After data collection, the researcher categorized the data based on the sources and analyzed them. The results of this study indicate that Efficiency has not been fully achieved due to mismatches in budget allocation. Meanwhile, transparency remains suboptimal because the existing system often experiences disruptions, limiting open access to information. The most dominant inhibiting factor affecting implementation effectiveness is human resources (HR). In addition, dependency on central government funding hampers flexibility and independence in regional financial management. The study suggests that BKAD should conduct technical competency training and development for staff, the Kupang City Government should increase local revenue (PAD), and the public should actively participate in budget public consultations.